2022
DOI: 10.1186/s42234-021-00083-7
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound neuromodulation on a multiwell MEA

Abstract: Background Microelectrode arrays (MEA) enable the measurement and stimulation of the electrical activity of cultured cells. The integration of other neuromodulation methods will significantly enhance the application range of MEAs to study their effects on neurons. A neuromodulation method that is recently gaining more attention is focused ultrasound neuromodulation (FUS), which has the potential to treat neurological disorders reversibly and precisely. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The limitation on quantitative measurement of ultrasound pressure in standing wave conditions can be addressed by a combination of simulation and optical methods. 45,46) Ultrasound stimulation with 39.5 and 500 kHz evoked Ca 2+ concentration changes inside neurons [Fig. 3(a), ] and it was similar to previously reported in vivo neuromodulation studies using sub-MHz ultrasound, where higher intensities were required for high-frequency stimulation.…”
Section: Discussionsupporting
confidence: 84%
“…The limitation on quantitative measurement of ultrasound pressure in standing wave conditions can be addressed by a combination of simulation and optical methods. 45,46) Ultrasound stimulation with 39.5 and 500 kHz evoked Ca 2+ concentration changes inside neurons [Fig. 3(a), ] and it was similar to previously reported in vivo neuromodulation studies using sub-MHz ultrasound, where higher intensities were required for high-frequency stimulation.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, the transient increase in neuronal activity we observed with the chemical PIEZO1 agonist, Yoda1, bears a resemblance to the reported effects of persistent low-frequency ultrasound on cultured hippocampal neurons cultured on microelectrode arrays. Saccher and colleagues reported that persistent exposure to focused ultrasound produced transient elevations in spontaneous network activity [ 54 ]. Calcium imaging studies offer a link between the effects of ultrasound stimulation and mechanosensitive channels, including but not limited to PIEZO1 channels [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To study more complex network responses, a higher-channel density MEA system must be designed to improve its sensitivity 18 . Several future directions for this proposed system have been identified, including using a 3D gantry to hold the transducer and ensure accurate placement 19 . Additional improvements could be made regarding the post-processing algorithm, including utilizing a spiking sorting algorithm 20 In conclusion, this system provides a high-throughput, in vitro platform for studying the neuro-modulatory effects of FUS on human neurons.…”
Section: Parameter Valuementioning
confidence: 99%